1988
DOI: 10.1159/000116296
|View full text |Cite
|
Sign up to set email alerts
|

Serum Immunoinhibitory Factors in Stroke Patients

Abstract: Immunoinhibitory factors in the sera of stroke patients were studied by an analysis of their capacity to influence the in vitro proliferative response of T cells. The evidence was obtained that the sera from stroke patients exhibited inhibitory activity on T cell proliferation. Although the nature of these inhibitory factors was not analyzed, it was clearly shown that their activity correlated with the degree of neurological defects, indicating that their determination may be of some prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
2
1
0
Order By: Relevance
“…Consistent with prior reports 31 , visual observations suggested decreased proliferative activity in lymphocyte cultures treated with unmanipulated ischemic stroke serum relative to those treated with unmanipulated serum from control groups, as they appeared to contain smaller and more diffuse clusters of blasting lymphocytes. However, visual indications suggested that the inhibitory effect of ischemic stroke serum was at least moderately counteracted by depletion of sCD163 (Fig.…”
Section: Resultssupporting
confidence: 89%
“…Consistent with prior reports 31 , visual observations suggested decreased proliferative activity in lymphocyte cultures treated with unmanipulated ischemic stroke serum relative to those treated with unmanipulated serum from control groups, as they appeared to contain smaller and more diffuse clusters of blasting lymphocytes. However, visual indications suggested that the inhibitory effect of ischemic stroke serum was at least moderately counteracted by depletion of sCD163 (Fig.…”
Section: Resultssupporting
confidence: 89%
“…Consistent with prior reports, 31 visual observations suggested decreased proliferative activity in lymphocyte cultures treated with unmanipulated ischemic stroke serum relative to those treated with unmanipulated serum from control groups, as they appeared to contain smaller and more diffuse clusters of blasting lymphocytes. However, visual indications suggested that the inhibitory effect of ischemic stroke serum was at least moderately counteracted by depletion of sCD163 ( Figure 5B).…”
Section: Stroke-induced Elevations In Circulating Scd163 Suppress Lymsupporting
confidence: 90%
“…Thereafter, strong evidence from clinical studies has shown that stroke causes a reduction of T cells in the peripheral blood and inhibition of T cell proliferation in response to antigen stimulation, as well as inhibition of the delayed type hypersensitivity (DTH) skin test [7]. Most studies agree that T-cell-mediated immunity is significantly inhibited by brain injury from stroke [7], [8], [9], [10], [11]. However, there are contradictory reports about the effects of stroke on humoral immunity in human patients.…”
Section: Introductionmentioning
confidence: 99%